The Purpose of Education from the Perspective of Hadith in Instilling Islamic Values Dynamically in Daily Life - Firmansyah Firmansyah (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
One of the main issues in today’s educational landscape is the tendency of society to view education merely as a means to achieve worldly goals, such as obtaining a job, career advancement, or social status. This narrow perspective has obscured the true essence of education, which should serve as a means of character building, strengthening moral values, and the pursuit of enlightening knowledge. To address this issue, it is essential to restore the essence of education as a process of humanizing individuals, in line with the noble values taught by religion. This paper is a library research study employing textual analysis and an interpretative approach. The data analysis method used is content analysis. Based on the discussion of the goals of Islamic education, it can be concluded that, according to hadith, education aims to develop strong faith and piety, instill noble morals and positive character, guide learners toward happiness in both this world and the hereafter, optimize human potential holistically, and dynamically embed Islamic values into daily life.